The Malaysian experience in science and technology development and its relevance for OIC countries - Abdul Murad, M.H.S. (2004)
The development of science and technology in Malaysia, like most developing countries, is state-led and state-driven, rather than a result of laissez-faire conditions. But in recent times, even in the developed world the development of science and technology has to some extent been influenced by the state. The existence of National Innovation Systems, and policies pertaining to the environment, testify to this. In Malaysia, our science and technology policy, which was first articulated in 1986 during the period of the Fifth Malaysia Plan, was designed as an integral part of the national economic policy, and not independently of it. The development of science and technology in other words, was meant to be an instrument for economic growth. Science and technology was to serve as an investment item and not as a consumption item. Thus government spending on S&T was closely related to those sectors which had been targeted by the government to serve as engines of economic growth. In the 1970s this was largely the agricultural sector, in the 1980s it began to shift towards the industrial sector (Hing Ai Yun 1986), and in the 1990s it shifted again towards the ICT industry (Dieter-Evers 2001). Thus developments in S&T closely parallels government efforts in economic development, and in some cases are even causally connected as in R&D expenditure in the agricultural sector, for example through government research institutes (GRI’s) such as the Rubber Research Institute (RRI), Malaysian Agricultural Research Institute (MARDI), and Palm Oil Research Institute of Malaysia (PORIM).